Article RETRACTED due to manipulation by the authors Analysis of injury risk levels in young footballers: A review of functional movement screens and static balance scores - Alexy Totti Fahrosi; Khoiril Anam; Anies Setiowati; Sugiarto Sugiarto; Nugroho Susanto; Tiok Wijanarko; Hendra Setyawan; Gema Fitriady; Özgür Eken; Zhanneta Kozina; Francesca Latino; Francesco Tafuri; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
: Injury or wound is damage to the structure or function of the body due to physical force or pressure. This study aims to analyze the risk of injury in young footballers in terms of the Functional Movement Screen (FMS) based on static balance scores. This study used a descriptive observational research method. The subjects were 31 young footballers (age 13.6±0.5 years, BMI 19.5±2.2 kg/m², TD 15.5±10 months). The data collection instrument involved FMS and Stand Stork Test (SST). The data were then analyzed using descriptive statistics. This study found that the FMS score with a high injury risk category was 6.45% in the SST poor category. Meanwhile, FMS scores in the moderate injury risk category were 19.35% in the SST moderate category, 32.25% in the SST poor category, and 3.25% in the SST very poor category. FMS scores in the low injury risk category were 6.45% in the moderate SST category and 32.25% in the poor SST category. The conclusion is that SPSS soccer academy students have a potential risk of injury in the moderate category and a static balance level in the less category. In addition, after reviewing the results of FMS scores based on SST scores, it can be concluded that FMS scores in the moderate category are found in samples with poor category SST, which is 32.25%. This study suggests improving static balance to prevent the risk of sports injuries in young footballers. Similar research in the future is also recommended, especially the one that uses other physical component variables and different research sample characteristics.